Examining the Implementation of Digital Marketing Strategies through the 4P Framework at a Trading Enterprise in Subang Regency, West Java - Siti Titta Partini (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
The rapidly advancing technology, particularly in information and the internet, catalyzes transformations across diverse sectors and business scales, including micro, small, and medium enterprises (MSMEs). The substantial contribution of MSMEs to national economic development and their rapid numerical growth underscores their capacity to enhance competitiveness via adaptation to change. PD. As an MSME, Mandiri is a peanut-based snack maker that employs digital marketing to adapt to technical advancements and shifts in consumer purchasing behavior and to address the challenge of diminishing sales. The study method employed a qualitative approach utilizing the 4P Model for analysis. Data collecting methodologies include observation, semi-structured interviews, and literature reviews. PD. Mandiri has a digital marketing approach based on the 4P framework: Product, Price, Place, and Promotion, utilizing social media platforms such as WhatsApp, Instagram, and Facebook, as well as marketplaces like Shopee and Tokopedia—data indicating the utilization of digital marketing by MSMEs PD. Mandiri has witnessed a substantial rise in sales volume.